2018
DOI: 10.5937/aaser1845061g
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of organic production of medicinal and aromatic plants in intercropping system

Abstract: Organic production of medicinal and aromatic plants is consistent with numerous regulations; hence it is under strict legal control. It implies a production system that does not disturb the naturally consistent balance of ecosystems in which plants are grown, taking into account the preservation of healing properties of derivatives obtained by further processing thereof. This production can be established on virgin lands, or those used for agricultural production but without the application of synthetic chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Intercropping in the organic cultivation of medicinal and aromatic plants seems to be a simple and very efficient method to reduce the occurrence of pests and diseases since the use of pesticides is not allowed in the organic production system. Plant cultivation in this system contributes to increased biodiversity, better utilization of natural resources, higher yields of many plants, and reduced abundance of weeds and pests [34].…”
Section: Discussionmentioning
confidence: 99%
“…Intercropping in the organic cultivation of medicinal and aromatic plants seems to be a simple and very efficient method to reduce the occurrence of pests and diseases since the use of pesticides is not allowed in the organic production system. Plant cultivation in this system contributes to increased biodiversity, better utilization of natural resources, higher yields of many plants, and reduced abundance of weeds and pests [34].…”
Section: Discussionmentioning
confidence: 99%
“…Gu et al [109] conducted a meta-analysis to determine the effect of multi-cropping on weed suppression and control. Other authors have shown that organically growing medicinal and aromatic plants as an intercrop is effective in reducing pests and diseases, increasing biodiversity, optimizing the use of resources, and increasing yields while at the same time increasing the resistance of the plants to pests and pathogens compared to sole crops, all of which helps to alleviate the challenges posed by weeds in organic farming systems [110]. The researchers selected data from 39 publications and drew several key conclusions.…”
Section: Weediness Of Multi-cropping System Cropsmentioning
confidence: 99%
“…A large number of MAPs, comprising anise, basil, caper, caraway, chamomile, chive, coriander, cumin, dill, fennel, fenugreek, lavender, lemon balm, lemon grass, licorice, marigold, marjoram, mint, parsley, rosemary, saffron, sage and thyme, are native to the MB [40]. Sustainable agricultural advantages of MAP cultivation include, improved soil health (soil organic nitrogen and carbon, soil water content, microbial activity and biomass), bio-pesticide and bio-herbicide control by allelopathic secondary metabolites, adaptability to diverse ecological conditions, including semi-arid conditions, with an added advantage to farmer profitability (essentials oil with high economic value) [41][42][43][44][45]. The potential benefits of intercropping with MAPs have been highlighted from studies, conducted mostly on vegetable crops, which have been subject to various reviews [42,43,46,47].…”
Section: Introductionmentioning
confidence: 99%